1984
DOI: 10.1038/jcbfm.1984.68
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte Extracts Enhance Neurogenic Vasoconstriction of Dog Cerebral Arteries in vitro

Abstract: Cerebral blood vessels of the dog have been shown to receive vasodilator and constrictor nerves. In isolated ring arterial preparations, neurogenic vasodilation was blocked while neurogenic vasoconstriction was potentiated by hemolysates isolated from hemolyzed erythrocytes. These results suggest that an overall increase in cerebral neurogenic vasoconstriction may occur in vivo following subarachnoid hemorrhage. The significance of this finding in the pathogenesis of cerebral vasospasm is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…3) without affecting VIPor CGRP-induced relaxation in isolated cerebral arteries [36,46]. These findings further support the notion that these two peptides were not the primary transmitters in mediating cerebral neurogenic vasodilation.…”
supporting
confidence: 76%
“…3) without affecting VIPor CGRP-induced relaxation in isolated cerebral arteries [36,46]. These findings further support the notion that these two peptides were not the primary transmitters in mediating cerebral neurogenic vasodilation.…”
supporting
confidence: 76%
“…It is known that, albeit limitations in studying a complex phenomenon such as SAH, the cerebral vascular ring-segment-mounted tissue bath method has supported most of the isolated in vitro work in cerebrovascular spasm (Lee et al, 1984;Cook, 1995). In our study, both PGE 2 -induced constriction and its potentiation by HbO 2 were blocked by neomycin, a phospholipase C inhibitor, and SC-19220, a selective EP 1 -receptor antagonist.…”
Section: Figmentioning
confidence: 52%
“…1416 " 19 Moreover, hemolysates have been reported to inhibit neurogenic vasodilation and to potentiate neurogenic vasoconstriction. 8 In the present experiments, AChinduced relaxation of the arterial rings from animals killed 4 days after the first SAH was inhibited by pretreatment with 10 ~6 M hemoglobin and completely abolished by 10~3 M hemoglobin. The present result is consistent with that seen in normal rabbit basilar arteries 7 and suggests that hemoglobin has basically the same inhibitory action on the ACh-induced relaxation in normal arteries and those exposed to SAH.…”
Section: Discussionmentioning
confidence: 74%
“…4 " 6 Moreover, in normal cerebral arteries, hemoglobin selectively inhibits endothelium-dependent vasodilation 7 as well as neurogenic vasodilation. 8 It is well documented that endothelial damage occurs frequently after SAH. We have recently demonstrated that endothelium-dependent vasodilation induced by adenosine triphosphate (ATP) is impaired after SAH in a rabbit single hemorrhage model (T. Nakagomi, unpublished data).…”
mentioning
confidence: 99%